Crossing the Innovation Chasm: Identifying Facilitators and Barriers to Early Adoption of the Global Health Starter Kit Curriculum. Issue 1 (22nd November 2021) - Lee, Jennifer; Tan, Ethan; Barrow, Jane; Bocala, Candace; Seymour, Brittany
Purpose: The Global Health Starter Kit (GHSK) is an interdisciplinary, competency-based, open access global health curriculum covering global disease and demographic trends, Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs), the connection between oral health and overall health, social determinants of health, and concepts of sustainable and ethical global health programs. In this study, we evaluate and describe barriers to and facilitators for using and implementing the GHSK curriculum across a variety of new users. Methods: This two-phase study uses the Roger's Adoption Curve concept to standardize this evaluation and inform a strategic plan for continuing to move the curriculum across the chasm from early adopters to an early majority of global oral health educators and learners. We utilized a theoretical adoption framework to identify facilitators and barriers under the domains of innovation and curricular, educator and learner, and institutional and structural factors. Under qualitative Phase 1, five early adopter institutions were interviewed to elicit understanding of factors that contribute to adoption of the GHSK curriculum. Common themes identified were next used to create a Phase 2 quantitative survey for early majority subscribers of the GHSK (N = 27). Results: These qualitative and quantitative results showed an overall high satisfaction with the quality of the GHSK materials, but also effectively identified barriers to its adoption, including inexperience of faculty in teaching global oral health, a lack of awareness and marketing, and absence of global health accrediting requirements. Conclusions: By identifying the barriers and facilitators of GHSK curriculum integration, this study provides concrete and specific opportunities to improve its format, relevance, content, and delivery. This study outlines next steps to creating a standardized approach to successfully adopting competency-based global oral health teaching and learning.